Home as an Emotional Construct in Romesh Gunesekeraâ€™s The Reef and The Sandglass - Mathur, University of Rajasthan, India, Charu (Asiatic: IIUM Journal of English Language and Literature, 2012)
Globalist discourse confounds the once clearly demarcated territorial borders of geography, national identity and belonging. This is more so in a diasporic situation that forces us to rethink concepts of nationalism, transnationalism and transmigration. Territorial belonging becomes complex for the traversals involved question the rigidity of identity itself. The categories of religion, ethnicity, gender and nationality become unstable. Diasporic identity emerges as a kind of unsettled space or an unresolved question in that space, between a number of intersecting discourses, and the location of belonging gets governed by these varying identities. Since identity itself is grounded in the huge unknowns of our psychic lives, memory plays a vital role in unravelling of the ways in which the discontinuities of time past and time present collapse spatial and temporal boundaries. Such deterritorialisation of the idea of homeland describes the disjunctions and fractured conditions of lived reality. The idea of nationhood and belonging is, therefore, always in a state of flux and mediated by personal and collective memories. Â Â Â The fiction of Romesh Gunesekera, a Sri Lankan writer now living in London, weaves together themes of memory, exile and postcolonial upheavals. The paper attempts to study two novels of Gunesekera,Â The ReefÂ (1994) andÂ The SandglassÂ (1998) and see how the territory of emotions determines the territory of longing and belonging in a diasporic situation. Being governed by location in time and place, the expatriateâ€™s feelings about â€œhomeâ€ are indelibly marked by his relationship with the home country. Located in London, the novels echo the histories, fugitive memories, crashed dreams and moments of promise that lie interwoven with lives lived in Sri Lanka.